ANALISIS RISIKO POSTUR KERJA PADA PEKERJA DI BAGIAN PEMILAHAN DAN PENIMBANGAN LINEN KOTOR RS. X - Seviana Rinawati (Universitas Darussalam Gontor, 2016)
This research objective is to determine and assess the valuation of REBA method in posture of workers in preventing disorders of the musculoskeletal. This study conducted using observational analytical research using qualitative descriptive analytic on a total sampling on workers in the laundry. Data were collected using a questionnaire and assessment form REBA be adjusted by Law no.1 1970. For the results, activities of weighing dirty laundry worker in the clothes in the category of low-risk level with a final score REBA is 3. While the activity of sorting dirty laundry clothes officers in the risk level high category with a final score REBA is 9, than required immediate action. For research conclusion, a high level of risk at this stage of the activity in the laundry attendant sorting soiled clothes caused by work postures of work attitude experiencing body twisting, bending and with the flexion. Advice given is the hospital attempts to control engineering, engineering management, administration procedures and procurement occupational health and safety promotion. Keywords: Rapid Entire Body Assessment (REBA); Work Posture